2003
DOI: 10.1124/jpet.103.053942
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Efficacy in Airway Disease Models ofN-(3,5-Dichloropyrid-4-yl)-[1-(4-fluorobenzyl)-5-hydroxy-indole-3-yl]-glyoxylic Acid Amide (AWD 12-281), a Selective Phosphodiesterase 4 Inhibitor for Inhaled Administration

Abstract: - [1-(4-fluorobenzyl)-5-hydroxy-indole-3-yl]-glyoxylic acid amide (AWD 12-281) is a highly potent and selective phosphodiesterase 4 (PDE4) inhibitor that was designed to have a metabolic profile that was optimized for topical administration. The aim of the current study was to explore the pharmacological profile of intratracheally administered AWD 12-281 in different models of asthma and chronic obstructive pulmonary disease (COPD) in comparison with steroids. To assess the anti-inflammatory potential of AWD 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 23 publications
3
58
0
2
Order By: Relevance
“…This extends previous work showing that the PDE4 inhibitors rolipram, roflumilast, cilomilast, and AWD 12-281 all attenuated allergeninduced pulmonary eosinophilia in the guinea pig (Banner et al, 1995;Underwood et al, 1998;Bundschuh et al, 2001;Kuss et al, 2003). In addition, we have demonstrated that RPL554 reduced the activation of eosinophils as assessed by the retention of EPO with eosinophils recovered in BAL.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This extends previous work showing that the PDE4 inhibitors rolipram, roflumilast, cilomilast, and AWD 12-281 all attenuated allergeninduced pulmonary eosinophilia in the guinea pig (Banner et al, 1995;Underwood et al, 1998;Bundschuh et al, 2001;Kuss et al, 2003). In addition, we have demonstrated that RPL554 reduced the activation of eosinophils as assessed by the retention of EPO with eosinophils recovered in BAL.…”
Section: Discussionsupporting
confidence: 88%
“…A variety of selective PDE4 inhibitors, including AWD 12-281 (Kuss et al, 2003), cilomilast (Underwood et al, 1998), roflumilast (Bundschuh et al, 2001), and the mixed PDE3/4 inhibitor zardaverine (Underwood et al, 1994), have been reported to significantly attenuate acute bronchospasm induced by antigen in sensitized guinea pigs. Likewise, CDP840 , but not rolipram, attenuated allergen-induced bronchoconstriction in the rabbit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of PDE3 seems to be more accurate target, but inhibitors of PDE4 are used more frequently, as it is documented by the number of studies. Application of selective PDE4 inhibitors (rolipram, roflumilast, cilomilast, piclamilast) significantly reduced the count of immune cells, amount of subepithelial collagen and influenced the epithelial hyperplasia [52]. Rolipram, which belongs to the 1 st generation of PDE4 inhibitors, did not meet the criteria for safe drugs, because of serious side effects.…”
Section: Selective Phosphodiesterase Inhibitors (Pde)mentioning
confidence: 99%
“…Addition of salmeterol caused additive blockade of adhesion mediated by eotaxin, a G-protein-activating chemokine, in eosinophils [18]. Other investigations have demonstrated that inhibition of PDE4 attenuates airway hyperresponsiveness and airway inflammation in sensitised mice [19,20]. Several studies have demonstrated attenuation of airway inflammation and airway reactivity by interaction of salmeterol with corticosteroids and steroid-sparing effects of theophylline [21,22]; however, little is known about the mechanism of action of PDE4 in b 2 -integrin-mediated adhesion in human PMNs.…”
mentioning
confidence: 97%